Gamificación en el desarrollo cognitivo de los niños de 4 a 5 años de la Unidad Educativa Francisco Huerta Rendón - Trujillo Moreno, Mayerly Suley (2023)
Gamification is the use of game elements and mechanics in non-gaming contexts, such as education. Its goal is to encourage participation, motivation and learning by including elements such as points, levels, rewards and competitions. The problem raised is the low participation and lack of interest of children aged 4 to 5 years in the Francisco Huerta Rendón Educational Unit, which can have a negative impact on their cognitive development and learning process. That is why the objective of this research is to determine gamification in the cognitive development of children aged 4 to 5 years from the Francisco Huerta Rendón Educational Unit. It is proposed to implement gamification strategies in teaching activities and methodologies to motivate children aged 4 to 5 years and increase their participation in the classroom. A non-experimental investigation was carried out on a population made up of 155 people, taking 5 teachers and 30 parents as a research sample. The results of this research support the adoption of gamified approaches in the educational environment, which contributes to improving the quality of education in general. In conclusion, it was determined that the implementation of gamification in the educational environment leads to a significant increase in the participation and interest of children aged 4 to 5 years in the Francisco Huerta Rendón Educational Unit, which is key to effective cognitive development.